2006
DOI: 10.1111/j.1365-2729.2006.00172.x
|View full text |Cite
|
Sign up to set email alerts
|

Making the cut: the impact of an integrated learning system on low achieving middle school students

Abstract: Research in integrated learning systems has demonstrated a need for rigorous studies that identify how such systems influence learning, and in particular that of low achieving students. No Child Left Behind legislation mandated evidence-based interventions as the standard for instructional approaches in American public schools. This quasi-experimental study investigated the impact of Merit literacy software on students in West Virginia. The study confirmed that the software supported the reading and language a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 13 publications
(11 reference statements)
0
7
0
Order By: Relevance
“…O'Byrne, Securro, Jones, and Cadle () used a quasi‐experimental study to investigate the impact of the literacy software ‘Merit’ on students in West Virginia. The collected data from one rural school and one urban school demonstrated that the software supported the reading and language arts curriculum and significantly improved the scores of low‐achieving middle school students on three variables of the WESTEST, a criterion‐referenced state test: reading and language arts, science, and social science.…”
Section: Related Workmentioning
confidence: 99%
“…O'Byrne, Securro, Jones, and Cadle () used a quasi‐experimental study to investigate the impact of the literacy software ‘Merit’ on students in West Virginia. The collected data from one rural school and one urban school demonstrated that the software supported the reading and language arts curriculum and significantly improved the scores of low‐achieving middle school students on three variables of the WESTEST, a criterion‐referenced state test: reading and language arts, science, and social science.…”
Section: Related Workmentioning
confidence: 99%
“…Instructional strategies commonly include guided feedback and practice (Wood et al, 1999), and repetition and rehearsal of content (O'Byrne, Securro, Jones, & Cadle, 2006). More sophisticated systems offer simulation (Kulik, 2003), multiple completion paths, and some opportunities for problem solving and decision-making (O'Byrne et al, 2006). Online (and of fl ine) supplementary material such as workbooks, manipulatives, third-party courseware, and "tool" software (word processing, database packages, etc.)…”
Section: See Also Computer-based Training and Management Systemsmentioning
confidence: 99%
“…Delivery of the ILS courseware content is computer-based, primarily utilizing drill-and-practice or tutorial approaches that are built on a foundation of behaviorist learning theory (Becker & Hativa, 1994;Wood, Underwood & Avis, 1999). Instructional strategies commonly include guided feedback and practice (Wood et al, 1999), and repetition and rehearsal of content (O'Byrne, Securro, Jones, & Cadle, 2006). More sophisticated systems offer simulation (Kulik, 2003), multiple completion paths, and some opportunities for problem solving and decision-making (O'Byrne et al, 2006).…”
Section: See Also Computer-based Training and Management Systemsmentioning
confidence: 99%
See 2 more Smart Citations